Runes from Lány (Czech Republic) - The oldest inscription among Slavs. A new standard for multidisciplinary analysis of runic bones. (March 2021) - Macháček, Jiří; Nedoma, Robert; Dresler, Petr; Schulz, Ilektra; Lagonik, Elias; Johnson, Stephen M.; Kaňáková, Ludmila; Slámová, Alena; Llamas, Bastien; Wegmann, Daniel; Hofmanová, Zuzana
Abstract: When Roman administration and legions gradually withdrew from the outer provinces after the fall of the Western Roman Empire, they created a power void filled by various groups. The dynamic Migration Period that followed is usually considered to have ended when the Germanic Lombards allegedly left Central Europe and were replaced by Slavs. Whether or how Slavic and Germanic tribes interacted, however, is currently disputed. Here we report the first direct archaeological find in support of a contact: a bone fragment dated to 600 AD incised with Germanic runes but found in Lány, Czechia, a contemporaneous settlement associated with Slavs. We documented and authenticated this artifact using a combined approach of use-wear analysis with SEM microscopy, direct radiocarbon dating, and ancient DNA analysis of the animal bone, thereby setting a new standard for the investigation of runic bones. The find is the first older fuþark inscription found in any non-Germanic context and suggests that the presumed ancestors of modern Slavic speakers encountered writing much earlier than previously thought. Graphical abstract: Image 1 Highlights: A rune-incised bone discovered in an Early Slavic context making it the first writing among Slavs. The find challenges the presumed sharp dicothomy between Germanic tribes and Early Slavs in Central Europe. Runology, radiocarbon dating and use-wear SEM microscopy authenticated the find. Target-enriched ancient DNA analysis allowed the bone to be identified as Bos taurus.